2017
DOI: 10.1038/ijo.2017.211
|View full text |Cite
|
Sign up to set email alerts
|

Presence of obesity is associated with lower mortality in elderly patients with implantable cardioverter defibrillator

Abstract: A paradoxical relationship between BMI and mortality risk is present in elderly patients with ICD at high risk of sudden death with a lower mortality in obese or overweight patients than in those with normal BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…Some previous studies also described an improved long‐term survival after CRT placement or ICD implantation, or combined CRT‐D placement, whereas other studies found similar outcomes among CRT in obese and non‐obese HF patients who received CRT therapy . Our study differs from prior ones in many aspects including the length of follow‐up (< 3 years), examination of CRT or ICD alone outcomes separately, population with inclusion of a limited number of patients (thus lacking the depth and diversity of our study population with respect to race, age or sex), or younger patients (< 65 years of age) than those included in our study (≥ 65 years) …”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Some previous studies also described an improved long‐term survival after CRT placement or ICD implantation, or combined CRT‐D placement, whereas other studies found similar outcomes among CRT in obese and non‐obese HF patients who received CRT therapy . Our study differs from prior ones in many aspects including the length of follow‐up (< 3 years), examination of CRT or ICD alone outcomes separately, population with inclusion of a limited number of patients (thus lacking the depth and diversity of our study population with respect to race, age or sex), or younger patients (< 65 years of age) than those included in our study (≥ 65 years) …”
Section: Discussionmentioning
confidence: 69%
“…Whether such an association is also observed in patients who receive CRT with defibrillator (CRT‐D) implantation is unclear. Some studies have described an improved long‐term survival among obese individuals who received CRT, whereas other studies found similar outcomes after CRT in obese and non‐obese patients . Other studies described lower death rates associated with a BMI > 25 kg/m 2 or an association of underweight or weight loss with higher death rates .…”
Section: Introductionmentioning
confidence: 99%
“…Sarcopenic obesity is a high-risk elderly syndrome that is mainly observed in elderly populations at risk of synergistic complications related to sarcopenia and obesity. Previously, sarcopenic obesity has been associated with a relatively higher risk of incident disability, comorbidities, and mortality [ 34 ]. Thus, introducing dietary interventions to optimize health status, especially for sarcopenic obese elderly persons in Korea, should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…(22,23). Although a paradoxical relationship between obesity (BMI) and mortality risk was also shown in elderly ICD-indicated patients at high risk of sudden death, the major cause of death was heart failure in this population (24).…”
Section: Discussionmentioning
confidence: 86%